Utilization of lymph node elastography in the axillary staging of breast cancer - Smolar, Marek; Kudelova, Eva; Danova, Ivana; Lucansky, Vincent; Dankova, Zuzana; Musova, Diana; Grendar, Marian; Nosakova, Lenka; Uhrik, Peter; Samec, Marek (Frontiers in Oncology, 2025)
BackgroundThe differential diagnosis of lymphadenopathy is an important determinant of prognosis in patients with breast cancer (BC). Invasive, fine needle aspiration (FNA) biopsy has been long considered as the gold standard for differentiating malignant lymph nodes (LN) from benign ones. Ultrasonography (USG) evaluation is a useful, rapid, and user-friendly imaging tool for LN assessment due to its high resolution. Compared to USG, ultrasound elastography is a relatively novel non-invasive method to differentiate benign and malignant lesions based on the stiffness heterogeneity of the tissue. The purpose of our study was to compare non-invasive imaging techniques, conventional USG, and strain elastography, to differentiate benign and malignant LNs lesions in a cohort of patients with early BC.MethodsIn total, 50 patients (48 women and 2 men) with histologically confirmed early BC were evaluated by conventional USG in B-mode followed by strain elastography (using parameters: pattern, strain ratio, hue histogram) for assessment of axillary LNs status. The surgical treatment included surgery of regional LNs (sentinel LN biopsy or axillary dissection), which served as the gold standard in statistical processing.ResultsThe USG B-mode was found to have a sensitivity of 68.75% and a specificity of 61.54%. Among strain elastography parameters, the elastographic pattern showed the highest specificity (66.67%) while the sensitivity was 83.3%. The strain ratio showed 100% sensitivity and 55.6% specificity, followed by a hue histogram with a sensitivity of 72.2%, but specificity was only 25.9%.ConclusionDespite promising data, monitored parameters currently cannot reliably replace sentinel LN biopsy. However, the monitored parameters represent an appropriate additional tool that can be used to refine preoperative staging, better targeting of FNA biopsy, and more accurate assessment of LNs in follow-up patients within the dispensary.